Assessment of Teachers’ Digital Literacy and Readiness for Effective Teaching in Oyo State - OKETUNBI, Okeyode Abraham; BADMUS, Olanrewaju Mukaheel (Ilorin Journal of Education, 2025)
The study investigated teachers’ digital literacy and readiness for effective teaching in Oyo State. A descriptive survey design was adopted to examine the availability and use of digital learning resources and their influence on teaching and learning effectiveness. The target population comprised 3,924 teachers and principals across public junior secondary schools in Oyo Educational Zone. A sample of 392 teachers representing 10% was randomly selected from 11 local government areas within the district. Two self-developed instruments were used: Digital Learning Resources Availability and Literacy Questionnaire (DLRALQ), Teaching and Learning Effectiveness (TLE) Questionnaire. Validity of the instruments was established by experts in Test and Measurement, and reliability was established using test-retest method. Three research questions were raised and answered using descriptive statistics, and two hypotheses were formula tested using inferential statistics. Findings revealed that the availability of digital learning resources was low, and in some cases, non-existent; teachers’ digital literacy levels were also low. However, the level of effective teaching and learning was high. There was a significant joint and relative influence of digital resource availability and teachers’ digital literacy on effective teaching and learning. The study concluded that despite low digital resource availability and limited teachers’ digital literacy, effective teaching and learning were moderate and significantly influenced by both variables. It was recommended that government should provide adequate digital learning resources through targeted funding and monitoring; teachers should receive continuous digital literacy training through in-service workshops and school administrators should establish ICT support units for proper maintenance and use of digital tools.